Pelatihan Tutor Paud Dalam Pembuatan Media Buku Flannel Berbahasa Inggris - Alfitriani Siregar (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
PAUD (Early Childhood Education) is a guidance process that determines the growth and development of children (3-6 years old) in the community. There are 10 PAUD of school in district of Medan Kota who are trained by PKK (Family Welfare Movement). They are trained about classroom setting, learning methods and health for children. The problems of tutor taught English by playing and singing without the tools. Team of community service with partners of BPTKI and HIMPAUDI discussed with a solution to provide training educator method English Language Educatif per word orally using Flanel Book products in child language development to tutors. Some methods of this activity were(1) Preparation for training activities, (2) implementation (action) by sewing and cutting patterns made from flannel materials into media as teaching tools, (3) observation of action by doing sewing skills and cut the pattern made into "flannel book", (4) Evaluation on readiness tutor using the product very well, (5) And the reflection is very enthusiastic on the activity of training can learn by other creativity with flannel material, because the flannel material is soft, odorless, not sharp , colorful, and safe for children.